Effectiveness of sublingual immunotherapy with house dust mite drops in asthmatic children at different ages - Tao Ai; Peilin Zhang; Ronghua Luo; Yinghong Fan; Wanmin Xia; Li Wang (Frontiers in Pediatrics, 2023)
BackgroundRespiratory allergies in children, such as asthma and rhinitis, are becoming progressively common every year. Recent studies found that pediatric patients with asthma receiving regular medication and specific immunotherapy (SIT) had improved therapeutic outcomes in a wide age range. However, there are few studies that have examined the effectiveness of SIT treatment in children with allergic asthma at different ages in terms of the degree of asthma control, improvements in lung function, and changes in exhaled nitric oxide (FeNO).MethodA total of 200 asthmatic pediatric patients who had been receiving regular treatment for at least a year were split into the observation and the control groups, which depended on whether sublingual immunotherapy was added based on conventional treatment medicines. The children who were divided by an age cut-off of 6 years old in these two groups were compared before and after therapy based on the exhaled levels of FeNO, pulmonary function, visual analog scale, medication scores, daytime and nighttime ratings of asthma symptom, and rhinitis symptom scores.ResultsBefore treatment, there was no significant difference between the observation group and the control group in various indicators of the patients under 6 years old; and in the older children (6–16 years old) group, the scores of FVC, FEV1, and FEF25 in the observation group were significantly lower than those in the control group (P < 0.05). The FEF75, FEF50, FEF25, and MMEF75/MMEF25 indexes in the observation group were significantly higher than those in the control group after treatment (P < 0.05), but there was no statistical significance in other indexes (P > 0.05). The scores of ACT, FEF75, FEF50, MMEF72/MMEF25, and FeNO in the observation group were all higher than those in the control group after treatment (P < 0.05), and the differences in other indexes were not statistically significant (P > 0.05). Between the young-age group and the elder group, there was no significant difference in all indexes in the observation group before and after treatment (P > 0.05).ConclusionChildren with asthma of all ages can considerably benefit from sublingual immunotherapy. Specifically, younger patients showed greater tendency on the improvement of small airway resistance, whereas school-age children with asthma significantly improved their small airway resistance as well as their asthma control and inflammation alleviation.